Communicating in groups applications and skills - Adams, Katherine; Galanes, Gloria; Hoelscher, Carrisa (McGraw-Hill Education, 2021)
"As we prepare this revision, the world seems to be falling apart-mass shootings in Orlando and San Diego; a trucker mowing down families in Nice, France; an attempted military coup in Turkey (although news is still coming in about what happened there). We humans somehow need to push the reset button on how we interact with one another and how we work together. Some of these despicable actions are the work of lone, disaffected individuals, but it is also true that many disaffected individuals are encouraged by groups working to disrupt a way of life they dislike."--Provided by publisher.